If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4(4x + -11) = 64 Reorder the terms: 2x + 4(-11 + 4x) = 64 2x + (-11 * 4 + 4x * 4) = 64 2x + (-44 + 16x) = 64 Reorder the terms: -44 + 2x + 16x = 64 Combine like terms: 2x + 16x = 18x -44 + 18x = 64 Solving -44 + 18x = 64 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + 18x = 64 + 44 Combine like terms: -44 + 44 = 0 0 + 18x = 64 + 44 18x = 64 + 44 Combine like terms: 64 + 44 = 108 18x = 108 Divide each side by '18'. x = 6 Simplifying x = 6
| (113-x)/2=30 | | A=28x-x^2 | | 7x+5(3x-17)=113 | | 8-6x=34 | | 6x+3=5x-16 | | 5x+2(4x-17)=83 | | 4x-16=28+36 | | x+x-5.3=718.7 | | 3y+30y=3 | | 9x^2-2y^2+18=0 | | -50=4m-2 | | 3x+3(3x-5)=45 | | -20+14=m-4 | | 3x+12=2x+15 | | 38x-4=5 | | 8-6x=37 | | -3y+5=-25 | | 25+0.25(65)= | | 100=x-0.15x | | x^2+x/6-2.5+0 | | 6y-3=6y+88 | | 7x+3(3x+4)=172 | | y=3x^2+11 | | 23.3=5n-4 | | 3=1+1 | | 5x=12/1/12 | | 6x+3(3x-5)=60 | | 7z+20=3z | | 7y+94.5=3 | | 7x+56=56 | | 2log(3x)+log(x+2)=log(9x^2+18x) | | 4.1=2.3-0.5y |